Memorial de Maria Moura: percurso crítico e representação da memória - Laile Ribeiro de Abreu (2011)
This dissertation intends to revisit the critique material available about Rachel de Queiroz, to study the presence of memory, of textual voices and of death in the work Memorial de Maria Moura (1992) by Rachel de Queiroz and to relate memory to order works by the author. In order to achieve these goals, the critique material about Rachel de Queiroz since her first novel, O Quinze (1930), until Memorial de Maria Moura (1992), will be discussed. Considering that the approach adopted here is about the authors last novel, the critique on it will be more deeply emphasized.Memory as an object of research is associated to a plurality of discursive voices, which brings up the discussion on polyphony and bakhtinian dialogism. Another topic approached here is the relationship between memory and death. Still on the scope of relationships with memory, this dissertation reveals that there are intersections between fictional texts and Rachel de Queirozs chronicles, which allows a comparison between them.